[1,4]-Aza-Brook Rearrangement for Efficient Formation of Benzynes and Their Cycloaddition - Huang, Ze-Ao; Tang, Fan; Xu, Yan-Jun; Lu, Chong-Dao (Synlett, 2015)
An efficient benzyne cycloaddition triggered by an aza-Brook rearrangement is reported. In this reaction, 2-(trimethylsilyl)aryl triflates bearing a benzylic secondary amine group at the 3-position undergo base-promoted [1,4]-carbon-to-nitrogen silyl migration (aza-Brook rearrangement) to generate benzyne intermediates, which are then trapped by intermolecular or intramolecular cycloaddition involving 1,3-dienes or 1,3-dipoles. This procedure furnishes various cycloadducts in yields of up to 99%.
Keywords: silyl migration; amines; aza-Brook rearrangement; benzyne, cycloaddition